Faktor-Faktor yang Berhubungan dengan Dismenorea pada Remaja PMR di SMA Negeri 5 Palopo Kota Palopo - Fadliyah Fadliyah; Fitri H. Sudiamin (Pusat Riset dan Inovasi Nasional, 2022)
Dysmenorrhea leads to a time when painful menstruation is generally felt by young female adolescents. Dysmenorrhea is felt within a few days before menstruation and lasts within a few hours and usually occurs within 2-3 days. To find out what factors are related to dysmenorrhea in PMR adolescents at SMA Negeri 5 Palopo in 2021. This study is an analytical cross sectional design. The population in this study is all students who participate in PMR activities at SMA Negeri 5 Palopo, sampling using Total Sampling, namely all populations are sampled as many as 50 respondents. Data collection uses questionnaire sheets and observation sheets. And the data collected was then processed using Microsoft excel programs and statistical programs (SPSS). Univariate analysis by looking for frequency distribution and bivariate analysis by Fisher's Exact Test with significance level (0.05). The results showed a relationship between the length of menstruation and dysmenorrhea in adolescents (p=,001). Nutritional status is related to dysmenorrhea in adolescents (p=,002). And there is a relationship between exercise habits and dysmenorrhea in adolescents (p=.002). The factors of menstrual age, nutritional status and exercise habits with dysmenorrhea in PMR adolescents have a relationship proven through statistical test data with a p value of ≤0.05.